Mechanisms of the anterior cruciate ligament injury in sports activities: A twenty-year clinical research of 1,700 athletes - Kobayashi, H.; Kanamura, T.; Koshida, S.; Miyashita, K.; Okado, T.; Shimizu, T.; Yokoe, K. (Journal of Sports Science & Medicine, 2010)
The mechanisms of anterior cruciate ligament (ACL) injuries are still inconclusive from an epidemiological standpoint. An epidemiological approach in a large sample group over an appropriate period of years will be necessary to enhance the current knowledge of the ACL injury mechanism. The objective of the study was to investigate the ACL injury occurrence in a large sample over twenty years and demonstrate the relationships between the ACL injury occurrence and the dynamic knee alignment at the time of the injury. We investigated the activity, the injury mechanism, and the dynamic knee alignment at the time of the injury in 1,718 patients diagnosed as having the ACL injuries. Regarding the activity at the time of the injury, "competition" was the most common, accounting for about half of all the injuries. The current result also showed that the noncontact injury was the most common, which was observed especially in many female athletes. Finally, the dynamic alignment of "Knee-in & Toe- out" (i.e. dynamic knee valgus) was the most common, accounting for about half. These results enhance our understanding of the ACL injury mechanism and may be used to guide future injury prevention strategies.